Environment Biological and Health Care Efforts Influenced of Lymfatic Filariasis Incidence, Sarmi Distric - Sipayung, Mina; Wahjuni, Chatarina Umbul; Devy, Shrimarti (Jurnal Berkala Epidemiologi, 2014)
ABSTRACTDistrict Sarmi is the most endemic area of filariasis in Papua which has rate of microfilaria (mf) (47.06%) up to the year2012. In the Province Papua filarial worm is Wuchereria bancrofti and is transmitted through the bite of a mosquito vectors. Lymphatic filariasis does not cause death, but in chronic cases it causes disability, psychosocial problems, stigma, and decreased productivity. This study was aimed to analyze environment biological and health care efforts that influence the incidence of lymphatic filariasis. This study used case-control method. Samples comprised 32 case samples (mf +) and 32 control samples (mf-). Primary data were collected through interviews and observation. Data were analyzed using Chi-Square and continued with multivariate Logistic Regression. Statistical analysis obtained indicated two variables on the incidence of lymphatic filariasis limfatik in District Sarmi (health care efforts pvalue = 0.002, OR: 7.779, as well as the biological environment pvalue= 0.008, OR: 5.841). Significant variables were health services with sub-variables promotion, prevention and the environmental biology. Suggestion: Mosquito bites should be avoided, the vector should be controlled through mutual cooperation and health promotion should be implemented.Keywords: Wuchereria bancrofti, lymphatic filariasis, vector, health care,                         Sarmi Distric